2008
DOI: 10.4049/jimmunol.181.9.6170
|View full text |Cite
|
Sign up to set email alerts
|

Human NK Cells Kill Resting but Not Activated Microglia via NKG2D- and NKp46-Mediated Recognition

Abstract: Microglia are resident macrophage-like APCs of the CNS. To avoid escalation of inflammatory processes and bystander damage within the CNS, microglia-driven inflammatory responses need to be tightly regulated and both spatially and temporally restricted. Following traumatic, infectious, and autoimmune-mediated brain injury, NK cells have been found in the CNS, but the functional significance of NK cell recruitment and their mechanisms of action during brain inflammation are not well understood. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 57 publications
0
73
0
Order By: Relevance
“…Thus, it is not well understood whether brain NK cells are the origin or the consequence of CNS pathogenesis. Some evidence suggests that NK cells can control CNS autoimmunity and inflammation by their capacity to kill autoreactive or proinflammatory microglia (5,12,14). Alternatively, NK cell response in CNS following infection may be deleterious (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is not well understood whether brain NK cells are the origin or the consequence of CNS pathogenesis. Some evidence suggests that NK cells can control CNS autoimmunity and inflammation by their capacity to kill autoreactive or proinflammatory microglia (5,12,14). Alternatively, NK cell response in CNS following infection may be deleterious (39).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NK cell physiology is modulated following the circadian rhythm through the influence of neurotransmitters, such as norepinephrine, which inhibits cytotoxic function after engagement of b-adrenergic receptors (11). Alternatively, NK cells could impact CNS physiology by killing glial cells (12) or by secreting IFN-g (13). Most knowledge about NK cells in the CNS is coming from studies of experimental autoimmune encephalomyelitis (EAE) where conflicting results are emerging, as NK cells have been shown to be either impli-cated in neuroprotection (14) or neurotoxicity (15).…”
Section: Nk Cells In Central Nervous System Disordersmentioning
confidence: 99%
“…2,3 The activating receptors recognize primarily stress-induced molecules on infected and transformed cells, including major histocompatibility complex (MHC) class I-like molecules that serve as ligands for the activating NK-cell receptor NKG2D, PVR and Nectin-2 as ligands for the activating NK-cell receptor DNAM-1, and B7-H6, as well as ligands of still poorly defined identity for the natural cytotoxicity receptors (NCRs) NKp30, NKp46, and NKp44. 4,5 Ligands for these activating receptors are up-regulated upon for example DNA damage or heat shock, 6,7 but are also constitutively present on some hematopoietic cells, including myeloid dendritic cells (DCs), 8 microglia, 9 and activated macrophages. 10 These activating signals are balanced by inhibitory receptor engagement, recognizing classical and nonclassical MHC class I molecules.…”
Section: Introductionmentioning
confidence: 99%
“…We used the To-Pro-3 incorporation assay as a measurement of direct cytotoxicity. 9,16,36 The NK-cell lines from hu-NSG mice killed K562 with high efficiency of more than 70% lysed cells already at a 10:1 NK:K562 ratio ( Figure 6B). This suggests that NK cells from hu-NSG mice are functionally competent, but require cytokine preactivation to reach their full functional potential.…”
mentioning
confidence: 99%
“…Recent studies showed also the ability of CD56 bright NK cells to kill other immune cells like immature DCs, immature microglia and activated macrophages , Della Chiesa et al 2003, Lunemann et al 2008). …”
Section: Effect Of Daclizumab On Nk Cellsmentioning
confidence: 99%